Influence of Ca2+ on tetracycline adsorption on montmorillonite - Parolo, Maria Eugenia (2012)
The adsorption of tetracycline (TC) on montmorillonite was studied as a function of pH and Ca 2+ concentration using a batch technique complemented with X-ray diffraction and transmission electron microscopy. In the absence of Ca 2+, TC adsorption was high at low pH and decreased as the pH increased. In the presence of Ca 2+, at least two different adsorption processes took place in the studied systems, i.e., cation exchange and Ca-bridging. Cation exchange was the prevailing process at pH<5, and thus, TC adsorption decreased by increasing total Ca 2+ concentration. On the contrary, Ca-bridging was the prevailing process at pH>5, and thus, TC adsorption increased by increasing Ca 2+ concentration. The pH 5 represents an isoadsorption pH where both adsorption processes compensate each other. TC adsorption became independent of Ca 2+ concentration at this pH. For TC adsorption on Ca 2+-montmorillonite in 0.01M NaCl experiments, the ratio adsorbed TC/retained Ca 2+ was close to 1 in the pH range of 5-9, indicating an important participation of Ca 2+ in the binding of TC to montmorillonite. X-ray diffraction and transmission electron microscopy showed that TC adsorption induced intercalation between montmorillonite layers forming a multiphase system with stacking of layers with and without intercalated TC.